Clinical research Prevalence of electrocardiographic abnormalities in patients with ischemic stroke, intracerebral hemorrhage, and subarachnoid hemorrhage - Lleva, Paul; Aronow, Wilbert; Amin, Harshad; Sandhu, Rasham; D’Aquila, Katharine (Archives of Medical Science, 2008)
Introduction: This study investigated the prevalence of electrocardiographic (ECG) abnormalities in patients with ischemic stroke (IS), subarachnoid hemorrhage SAH), and intracerebral hemorrhage (ICH) without chest pain or evidence of recent myocardial infarction (MI). Material and methods: The patients included 169, mean age 67 years, with IS, 100, mean age 61 years, with ICH and 101, mean age 51 years, with SAH. All diagnoses were confirmed by magnetic resonance imaging or brain computed tomography. Patients with chest pain or a diagnosis of acute MI were excluded from the study. Twelve-lead ECGs were taken at the time stroke was diagnosed. All ECGs were interpreted by a cardiologist experienced in interpreting ECGs. Results: Deep T wave inversion in the precordial leads was present in 0% of IS patients, 5% of SAH patients, and 5% of ICH patients. ST-segment depression was present in 17% of IS patients, 17% of SAH patients, and 26% of ICH patients. Left ventricular hypertrophy was present in 14% of IS patients, 8% of SAH patients, and 22% of ICH patients. Old Q-wave MI was present in 23% of IS patients, 6% of SAH patients, and 20% of ICH patients. Conclusions: Deep T wave inversion in the precordial leads was present in 0% of IS patients, 5% of SAH patients, and 5% of ICH patients.